The effect of using picture series in contextual grammar teaching on student’s writing skill - Fikni, Zahratul; ., Usuluddin; Marzuki, M Junaidi; Aini, Muadatul (Journal of English Language and Education, 2025)
This study aims to determine the effect of contextual grammar teaching using picture series on high school students' writing skills. While contextual grammar approaches and visual media have been widely discussed, limited studies integrate both to enhance writing skill. This study employed a quantitative approach with a pre-experimental research design. The population consisted of 16 tenth-grade student at SMA NWDI Pringgabaya in the 2024/2025 academic year. Writing tests were for data collecting, consisting of a pre-test and a post-test. The data analysis showed that pre-test score was 55.38, while the post-test score was 66.88. A paired sample t-test analysis showed that a significance value of 0.000 0.05, indicating a significant difference between the students' pre-test and post-test results. Thus, it is can concluded contextual grammar learning using picture series has effective in improving high school students’ writing skills.